A penalty method for constrained multibody kinematics optimisation using a Levenberg–Marquardt algorithm. Issue 7 (19th May 2023) - Livet, Claire; Rouvier, Théo; Sauret, Christophe; Pillet, Hélène; Dumont, Georges; Pontonnier, Charles
Abstract: An alternative method for solving constrained multibody kinematics optimisation using a penalty method on constraints and a Levenberg–Marquardt algorithm is proposed. It is compared to an optimisation resolution with hard kinematic constraints. These methods are applied to two pairs of experiments and models. The penalty method was at least 20 times faster than the optimisation resolution while keeping similar reconstruction errors and constraints violation. The potential of the method is shown to accurately solve the multibody kinematics optimisation problem in a reasonable amount of time. A computational gain lies in implementing this resolution with a compiled and optimised program code.